A Phenomenological Approach to Understanding Different Perceptual Interests: Interactions Between Endometriosis Patients and Their Physicians - Shirley Huang; Sarah Caston (Journal of Integrative and Innovative Humanities)
Understanding patients’ experiences of illness is critical to successful and holistic treatment. It is especially important in illnesses associated with diagnosis delays and mismanagement, like endometriosis. Endometriosis affects ten percent of reproductive age females globally but remains poorly recognized due to a lack of understanding from society and the healthcare system, an under-appreciation of women’s pain, and stigmatization. The broader structural implications of the paucity in research and physician training reveal neglect of patient embodiment and denial of women’s pain within medicine. By focusing on the history of endometriosis, the way it has been conceptualized through patient and physician perspectives, and the way it is part of a larger history of dismissing women’s pain, we examine the ways in which a phenomenological approach bridges the differences in perception between patient and physician as well as patient and society.